TRADISI CUCI KAKI (DOHU TIODO) DI DESA BOSSO KECAMATAN GANE BARAT UTARA KABUPATEN HALMAHERA SELATAN - Richardo Tobeoto (Universitas Sam Ratulangi, 2023)
Indonesia is known for its diversity of traditions and cultures. Indonesian society is also a society that highly values and upholds cultural values that are inherited from ancestors from the past and tries to preserve them. The existence of tradition is a universal cultural phenomenon in the life of every human being who lives in society. As evidence of these cultural phenomena, tradition is a depiction of the situation, behavior, norm values and customs of a particular society. One of the traditions that still exists and is still being carried out and is still upheld by the value contained in it is the Foot Washing Tradition, this tradition is carried out by the Tobelo ethnic community, Gelela for girls who have married boys from the Tobelo tribe, Galela in Bosso Village, North West Gane District, South Halmahera Regency. The purpose of this foot washing tradition is to introduce their son-in-law (son-in-law) to the family and also the community, provide protection for the son-in-law so that the community and family respect, act in accordance with norms, or in accordance with the culture that prevails in the community, do not do anything arbitrary to him and also raise the status of his son-in-law among the community. If the tradition has been carried out and there is a community or family that violates it, it will be subject to a fine or commonly called a customary fine. Keywords: tradition, foot wash, mohoka